System dynamics model for evaluation of reuse of electronic waste originated from personal computers - Simonetto, Eugenio; Quelhas, Osvaldo; Spasojević Brkić, Vesna; Putnik, Goran; Castro, Hélio (Serbian Journal of Management, 2016)
Information and Communication Technologies (ICT) are part of the day to day activities of a large part of world population, however its use involves a growing generation of electronic waste (e-waste).Due to the increasing technological innovation, it occurs that in a short time, the products become obsolete and have their life cycle reduced. The article aims to present the development, verification and validation of models of computational simulation for assessment of environmental and financial impacts caused by the extension of the life cycle of personal computers (PC) through their remanufacturing. For the system modeling the System Dynamics theory was used. Results generated by the simulation model, show that the remanufacturing is a viable alternative for the reutilization of discarded computers and that it is possible, in advance, to discuss, assess and decide necessary measures for a better financial and environmental performance in the acquisition and use of ICT.